Proposal for improving inventory replenishment through lean tools in a peruvian retail company - Jiménez Loaiza, Marysell (2024)
The purpose of this research work is to improve the replenishment of inventories in a retail company, due to is essential for any company to meet the demand for the product. This is why through the percentage of canceled orders in the retail company and by an Ishikawa diagram it was determined that the problem was that they did not have distribution centers so the logistics process produced cost overruns. Through the methodology applied the improvement proposal is divided into three stages, which consist of the collection of information and diagnosis of Hubs logistics, the design, and validation of the improvement proposal, and finally the viability, risks, and times it would take to execute the proposal. These stages determine that the solution to take would be to place a logistics hub that would support distribution as a low-cost warehouse. It is concluded that it is feasible to implement the Hub, which would increase the availability of merchandise, as well as the assortment, and save on transportation from the distribution center of Lima to the Hub located in Tarapoto.